Evaluation of Eucheuma cottonii and Gracilaria sp. as Food Buffer for The Ibu Kota Nusantara (IKN) Based on Proximate Analysis - Gevbry Ranti Ramadhani Simamora; Amalia Nur Kumalaningrum; Siti Munfarida; Olga Galih Rakha Siwi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
East Kalimantan Province has great opportunities as a buffer for the IKN economy based on the utilization of marine potential. Eucheuma cottonii and Gracilaria sp. are the red seaweeds (Rhodophyta) most widely cultivated in Indonesia. This study aims to analyze the proximate content in two types of red seaweed, namely E. cottonii (offshore cultivation) and Gracilaria sp. (pond cultivation) obtained from farmers in dry conditions cultivated around the waters of Balikpapan, East Kalimantan, Indonesia. The results of the analysis showed significant differences between cultivation locations. Gracilaria sp. (pond cultivation) taken from Handil (HTK) and Babulu Laut (BALUKE) is considered potential because it has low water content (HTK 26.99 ± 0.02%), and has higher ash content (BALUKE 31.18 ± 0.41%), fat (BALUKE 0.36 ± 0.01%), protein (BALUKE 10.01 ± 0.01%), and crude fiber (HTK 1.90 ± 0.16%) compared to E. cottonii. These findings provide important information for the development of seaweed as a natural resource for the food and health industries. Keywords: Eucheuma cottonii, Food industry, Gracilaria sp., proximate content, Red seaweeds